2021
DOI: 10.1111/eva.13298
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chromosome 4 and mercury accumulation in muscle of the three‐spined stickleback (Gasterosteus aculeatus)

Abstract: Anthropogenic stressors, such as pollutants, act as selective factors that can leave measurable changes in allele frequencies in the genome. Metals are of particular concern among pollutants, because of interference with vital biological pathways.We use the three-spined stickleback as a model for adaptation to mercury pollution in natural populations. We collected sticklebacks from 21 locations in Flanders (Belgium), measured the accumulated levels of mercury in the skeletal muscle tissue, and genotyped the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 93 publications
2
13
2
Order By: Relevance
“…Moreover, local selection may have contributed more to population differentiation in native species. For instance, local pollution may be genotoxic, select for tolerant genotypes, cause local bottlenecks, or alter migration patterns (Calboli et al, 2021; Costa, 2021; Díez‐del‐Molino et al, 2018). The variation in IBD patterns may also be attributed to variation in effective population size.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, local selection may have contributed more to population differentiation in native species. For instance, local pollution may be genotoxic, select for tolerant genotypes, cause local bottlenecks, or alter migration patterns (Calboli et al, 2021; Costa, 2021; Díez‐del‐Molino et al, 2018). The variation in IBD patterns may also be attributed to variation in effective population size.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of sampling sites, sample collection, sample preparation, sex determination, and measurement of mercury content in muscle tissue and in the sediment is available in Calboli et al (2021). Here, we provide a summary of these methods, and describe additional procedures relevant for our study.…”
Section: Methodsmentioning
confidence: 99%
“…Flanders has experienced a significant degree of metal pollution from industrial activities since the 19th century, with very local though scattered signatures of mercury contamination in soils and sediments (Tack et al, 2005; Van Steertegem, 2011, Brosens et al, 2015). Accordingly, mercury concentrations in the muscle tissue of stickleback populations are highly variable, ranging from 21.5 to 327 ng/g dry weight (Calboli et al, 2021). Calboli et al (2021) further revealed that Hg accumulation is associated with specific genomic regions, suggesting a genetic basis for adaptation to mercury-polluted environments in three-spined sticklebacks in Flanders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of chemicals or heavy metals disrupt metabolic pathways and biological functions, and as such, the pressure imposed is direct and directional for increasing tolerance. With that in mind, Calboli et al (2021) performed a genome-wide association study to investigate the genetic basis of mercury tolerance in sticklebacks (Gasterosteus aculeatus) collected along a gradient of polluted environments. Exploring an association between mercury in muscle tissue and genome-wide genomic variants, Calboli et al found localized genomic regions putatively involved in adaptation to mercury-polluted environments.…”
Section: Pollution and Multistressor Environments Of Urbanized Areasmentioning
confidence: 99%